Biblical Sources of Ecclesiology in Expositio Symboli Apostolorum by Johannes Marienwerder - Karczewski, Marek (Studia Warmińskie, 2022)
The structure of the article: the first section discusses the significance of Expositio in the light of other work by Johannes Marienwerder. The second section is concerned with the principal qualities of the Church in their relation to the Scripture, so as to examine the ecclesiological element in the interpretation of the Article 9 of the Apostles’ Creed and in the remainder of Expositio. That section concludes with findings from the analysis of how biblical texts are used in Marienwerder’s ecclesiological disquisition. Finally, attention is drawn to the relation between the conception of the Church in Expositio and the reformatory postulations advanced in the ecclesiastical and scholarly circles of Bohemian Prague in the second half of the fourteenth century. The mission of the Church is closely aligned with the biblical testimonies, which shed light on its nature and the purpose of its existence. The Holy Scripture also provides knowledge about the principal characteristics of the Church: unity, dignity and constancy. The biblical texts also supply a foundation thanks to which the errors and heresies directed against the Church can be repudiated. The considerably emphasized importance of the Scripture was characteristic of the new theology deriving from the current of devotio moderna. This study constitutes a preliminary to further research on the ecclesiology of Marienwerder.